Los nuevos vándalos y la Redacción Periodística - López de Zuazo Algar, Antonio (Estudios sobre el Mensaje Periodístico, 2002)
The terrorist Osama bin Laden, allied of the taliban in Afghanistan, said: “We will reconquer the Al Andalus”, Andalucía, the land of the vandals.
Keywords: Vandals; alans; Carthage; Roma; Ostia; Constantinople; Stilicon; Genseric; Huneric; Eudoxia; Belisario; Hugo; Flaubert; pillage; orthography; Writing Journalism; Latin; Spanish; woman; teletext